Anatomical and phytochemical study of Ocimum basilicum L. leaves of two popular varieties in Ukraine - Pysklynets , Iryna; Makhinya , Larysa (The Ukrainian Scientific Medical Youth Journal, 2024)
оne of the important sources of flavonoid phytonutrients is basil (Ocimum basilicum L.). Vegetative and generative organs of which have essential oils, in particular 1,8-cineole, estragole and eugenol, ascorbic acid, a rich pigment complex, as well as polyphenolic compounds with antioxidant effects. Basil realizes its antioxidant potential through anthocyanins in varieties with purple leaves and flavonoids in varieties with green leaves. The level of their accumulation, as well as other biologically active substances, depends on the variety to which the plant belongs, the degree and spectrum of illumination, soil moisture, and mineral nutrition (Priss OP, et al., 2019; Joshi RK, 2014; Trichopoulou, et al., 2000). That is why our attention was drawn to two of the most popular basil varieties in Ukraine: "Dolly" with green leaves and "Rosie" with purple leaves. Our research was focused on morphological, anatomical and phytochemical studies of O. basilicum leaves of the above-mentioned raw materials. To realize this goal, microscopy was performed using State Pharmacopoeia of Ukraine methods. Groups of biologically active substances were determined by standard qualitative reactions and the procedure was carried out using extracts or by applying directly to the sections. It was found that O. basilicum chanterelles of "Dolly" and "Rosie" varieties have a number of common and distinctive features. Both varieties of O. basilicum are characterized by the presence of dorsoventral, amphistomatic leaves, diacytic stomatal apparatus and biserial glands. The leaves differ in color, shape of the leaf blade margin, outlines of the upper epidermal cells, presence of idioblast cells with anthocyanins in the "Rosie" variety, and values of stomatal indices. The stomatal index is 27.5±2.3% for the "Dolly" variety and 25.4±2.5% for the "Rosie" variety. It was found that the leaves of O. basilicum varieties "Dolly" and "Rosie" contain such biologically active substances as anthocyanins, flavonoids, essential oil, triterpene saponins, especially expressed in the variety "Rosie" and tannins. The research results can be used in the development of a monograph on the raw materials of this species.